PURSUING SOCIAL JUSTICE IN ELA : a framework for negotiating the challenges of teaching - LILLGE, DANIELLE ([S.l.] : ROUTLEDGE, 2022)
Challenges arise when teachers seek to enact socially just instruction while navigating social, classroom, and school dynamics. This research-based, field-tested text offers an accessible process for successfully negotiating these dynamics to identify consequential inroads for making positive educational change. With a focus on ELA instruction, but applicable to other content areas, Lillge's clear framework offers a language for naming, and practical tools for navigating, those spaces where different frameworks for teaching and learning challenge teachers' ability to act on their commitments to teach for justice. Throughout the book, readers meet teachers who show how they reframed challenges and identified opportunities to work with others within inequitable systems to enact more just and equitable teaching. These case studies in teachers' own words allow readers to analyze how context and classroom culture influence teachers' negotiation processes. Serving as more than thought-provoking exemplars of what to do, the case studies and spotlighted "application moments" also invite readers to reflect on their own negotiations in the fieldwork, classrooms, and professional learning communities where they teach and learn. Comprehensive and illuminating, this book is a vital resource for pre-service teachers, teacher educators, and novice teachers.
Keywords: EDUCATION / General; Language arts; English language -- Study and teaching -- Social aspects; Social justice and education